Application of enhanced recovery after surgery in partial nephrectomy for renal tumors: A systematic review and meta-analysis - Wangjian, Wu; Tianyi, Lu; Xiaoqian, Ma; Di, Zhang; Chuan, Zhou; Chao, Wang; Zijian, Da; Tongtong, Jin; Fenghai, Zhou (Frontiers in Oncology, 2023)
Objectives Recently, ERAS has been widely used in the field of urology, especially in radical cystectomy and radical prostatectomy, and has demonstrated its advantages. Although studies on the application of ERAS in partial nephrectomy for renal tumors are increasing, the conclusions are mixed, especially in terms of postoperative complications, etc, and its safety and efficacy are questionable. We conducted a systematic review and meta-analysis to assess the safety and efficacy of ERAS in the application of partial nephrectomy for renal tumors. Methods All published literature related to enhanced recovery after surgery in partial nephrectomy for renal tumors from Pubmed, Embase, Cohrance library, Web of science and Chinese databases (CNKI, VIP, Wangfang and CBM) from the date of establishment to July 15, 2022 were systematically searched. Results This meta-analysis included 35 literature, including 19 retrospective cohort studies and 16 randomized controlled studies with a total of 3171 patients. The ERAS group was found to exhibit advantages in the following outcome indicators: postoperative hospital stay (WMD=-2.88, 95% CI: -3.71 to -2.05, p<0.001), total hospital stay (WMD=-3.35, 95% CI: -3.73 to -2.97, p<0.001), time to first postoperative bed activity (SMD=-3.80, 95% CI: -4.61 to -2.98, p < 0.001), time to first postoperative venting (SMD=-1.55, 95% CI: -1.92 to -1.18, p < 0.001), time to first postoperative bowel movement (SMD=-1.52, 95% CI: -2.08 to -0.96, p < 0.001), time to first postoperative food intake ( SMD=-3.65, 95% CI: -4.59 to -2.71, p<0.001), time to catheter retention (SMD=-3.69, 95% CI: -4.61 to -2.77, p<0.001), time to drainage tube retention (SMD=-2.77, 95% CI: -3.41 to -2.13, p<0.001), postoperative complication incidence (RR=0.41, 95% CI: 0.35 to 0.49, p<0.001), postoperative bleeding incidence (RR=0.41, 95% CI: 0.26 to 0.66, p<0.001), postoperative urinary leakage incidence (RR=0.27, 95% CI: 0.11 to 0.65, p=0.004), deep vein thrombosis incidence (RR=0.14, 95% CI: 0.06 to 0.36, p<0.001), and hospitalization costs (WMD=-0.82, 95% CI: -1.20 to -0.43, p<0.001). Conclusion ERAS is safe and effective in partial nephrectomy of renal tumors. In addition, ERAS can improve the turnover rate of hospital beds, reduce medical costs and improve the utilization rate of medical resources.